GENDER AND CLASS IN SALLY ROONEY’S NORMAL PEOPLE - Damia Rizka Ghassani; Ida Farida Sachmadi; Lestari Manggong (UIN Alauddin Makassar, 2023)
Normal People (2018), a novel by Sally Rooney, presents issues of gender and class through its description of two different perspectives of the main characters, Connell and Marianne. This article examines how this novel depicts issues of gender and class which are portrayed through Connell and Marianne’s relationship as a couple. Using narrative theories by Bal and Genette, as well as Haslanger’s and Raewyn Connell’s theory on gender and Bourdieu’s theory on social class, this article focuses on how the discrimination of gender and class affects Connell’s and Marianne’s relationship. The findings and discussion show the oppression that Marianne experiences is associated with the internalization of oppression, sexism, and misogyny. The discussion also shows that hegemonic masculinity has a role in the matter of how the difference of Connell’s and Marianne’s gender and class is presented. Despite being superior in term of class, Marianne is inferior in term of gender than Connell who comes from a working class society. However, the novel presents how the main characters’ perception changes as in the end they no longer problematize their gender and class. We argue that the novel disagrees with the inferior feeling caused by different gender and class.